PEMANFAATAN FLAG SECURE UNTUK PROTEKSI BUKU DIGITAL PADA E-LIBRARY INSTITUT TEKNOLOGI DIRGANTARA ADISUTJIPTO - sudaryanto sudaryanto (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2022)
Documents in the E-library service at the Adisutjipto Institute of Aerospace Technology (ITDA) Library are available and can be accessed and read by library members via a computer connected to the E-library network. So that the existing e-library can be accessed by many people with mobile computing equipment, it is necessary to make software that can access documents in the E-library in the form of a book in the Protable Document Format (PDF) format. The purpose of this research is to make books in PDF format so that they can be accessed and read and protected from being reproduced without the permission of the ITDA library. The method used in this research is in the form of software design with object-oriented programming, by dividing the application into small parts / objects into a large application that is used to access e-libraries with mobile computing devices. The application created also uses a library in Android Studio called the secure flag. The results of the tests carried out stated that the protection of book files in the android-based e-library application was able to prevent users from taking screenshots, copying book files, and downloading files illegally, while the speed of access in opening book files in e-library-based applications android is greatly influenced by connection speed and book file size. From the results of this test, it can be concluded that books in PDF format in the E-library in the ITDA Library can be protected.